What is qualitative interviewing? - Edwards, Rosalind; Holland, Janet (2013)
This text makes clear the procedures and practices surrounding qualitative interviewing. Qualitative interviews are a critical part of qualitative research, but understandings of what it means to carry out interviews have shifted over time. It provides the latest studies and practical guidance on how to cater for a broad range of research. It shows researchers and students how to begin with key questions and theories and the best interviewing tactic to take.
What do the key terms used about qualitative interviews mean? -- How have qualitative interviews developed? -- What forms can qualitative interviews take? -- Where can qualitative interviews take place? -- What sort of research tools can be used in conducting qualitative interviews? -- What are the practicalities involved in conducting qualitative interviews? -- What are the power and emotional dynamics of qualitative interviews? -- What are the strengths, challenges and future of qualitative interviews?
Includes bibliographical references (pages 99-124) and index.
Keywords: Social sciences -- Research -- Methodology; Interviewing; Sciences sociales -- Recherche -- Méthodologie.; Entretiens; Interviewing; Social sciences -- Research -- Methodology